What does the Bible say about suffering? - Gregg, Brian Han (Downers Grove, IL : IVP Academic, an imprint of nterVarsity Press, 2016)
The quest for an answer to the problem of suffering is universal. People often treat Scripture like a manual, looking for a single clear response that explains the presence of evil and suffering. Brian Han Gregg thinks we should take a different approach. The Bible does not have one but many responses to suffering. To pick out one theme is to hear the sopranos but miss the choir. We need to listen to the whole biblical narrative to appreciate its multifaceted handling of the problem. What Does the Bible Say About Suffering? explores twelve themes related to the issue of human suffering and reflects on what we can learn from the diversity of the biblical witness. Readable and informed by biblical scholarship, this book is a timely resource for students, small groups and anyone looking for a fresh approach to a topic of perennial interest.
The two ways: suffering and the God of justice -- Sin is lurking at the door: suffering and choice -- The purposes of God: suffering and the sovereignty of God -- The accuser: suffering and the devil -- I am: the mystery of suffering -- God wins: suffering and the future -- Running the race: suffering as training -- Confronting the truth: suffering as testing -- Jars of clay: suffering and the power of weakness -- Pass it on: suffering and the comfort of God -- The cruciform path to glory: following God into suffering -- To suffer for another: participation in the suffering of God.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Suffering -- Biblical teaching; RELIGION -- Christian Theology -- General; Suffering -- Biblical teaching; Electronic books